FAKTOR-FAKTOR PENENTU EMPLOYABILITY SKILLS MAHASISWA DALAM PENDIDIKAN TINGGI: STUDI SYSTEMATIC LITERATURE REVIEW - Muhamad Suhardi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT The changing competency demands of the workforce in the transition from the Industrial Revolution 4.0 to Society 5.0 have positioned employability skills as a key indicator of higher education graduates' work readiness. Despite this growing importance, numerous studies continue to report a mismatch between graduates' competencies and industry expectations, while empirical evidence regarding the factors shaping employability skills remains fragmented and lacks comprehensive synthesis. This study aims to identify, classify, and synthesize the factors influencing university students' employability skills, while also determining the factors most consistently reported across the existing literature. A Systematic Literature Review (SLR) approach was employed through the processes of identification, selection, classification, and descriptive synthesis of 20 scholarly articles retrieved from the Scopus, Google Scholar, and ScienceDirect databases, published between 2022 and 2026. The synthesis revealed that psychological attributes and learning experiences constitute the most consistent determinants of employability skills, whereas the contribution of technical competencies tends to vary when not supported by non-technical competencies. These determinants include soft skills, work motivation, self-efficacy, emotional intelligence, psychological capital, internship experience, social support, learning environment, and educational programs. This study contributes a conceptual synthesis demonstrating that employability skills evolve through the interaction of personal and contextual factors, highlighting the need for integrated learning strategies that are responsive to the evolving demands of the labor market. ABSTRAK Perubahan kebutuhan kompetensi di dunia kerja pada era Revolusi Industri 4.0 menuju Society 5.0 menempatkan employability skills sebagai salah satu indikator utama kesiapan lulusan perguruan tinggi. Meskipun demikian, berbagai penelitian masih melaporkan kesenjangan antara kompetensi lulusan dan kebutuhan industri, sementara bukti empiris mengenai faktor-faktor yang membentuk employability skills masih tersebar dalam berbagai kajian dan belum terintegrasi secara komprehensif. Penelitian ini bertujuan mengidentifikasi, mengklasifikasikan, serta mensintesis faktor-faktor yang memengaruhi employability skills mahasiswa sekaligus mengidentifikasi kecenderungan faktor yang paling konsisten dilaporkan dalam literatur. Pendekatan Systematic Literature Review diterapkan melalui proses identifikasi, seleksi, klasifikasi, dan sintesis deskriptif terhadap 20 artikel ilmiah yang diperoleh dari basis data Scopus, Google Scholar, dan ScienceDirect dengan rentang publikasi 2022–2026. Sintesis memperlihatkan bahwa determinan psikologis dan pengalaman belajar merupakan kelompok faktor yang paling konsisten membentuk employability skills, sedangkan kontribusi kompetensi teknis cenderung lebih bervariasi apabila tidak didukung kompetensi nonteknis. Faktor-faktor tersebut mencakup soft skills, motivasi, self-efficacy, emotional intelligence, psychological capital, pengalaman magang, dukungan sosial, lingkungan belajar, dan program pendidikan. Penelitian ini menawarkan sintesis konseptual yang menegaskan bahwa employability skills berkembang melalui keterkaitan antara faktor personal dan kontekstual, sehingga pengembangannya memerlukan strategi pembelajaran yang terintegrasi dan adaptif terhadap dinamika kebutuhan dunia kerja.